Exploring The Accessibility of Shopee Pay Later And Public Income On Cash Withdrawal Behavior - Anindya Putri Istiqomah; Yulianti, Ida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The Buy Now, Pay Later (BNPL) service in e-commerce transactions is increasingly being misused to obtain cash. This credit card cash swiping practice in Indonesia is commonly known as gesek tunai (gestun). This study analyzes the effects of community income and the ease of accessing Shopee Pay Later on purchasing behavior. The findings of this study can serve as a reference for Bank Indonesia in formulating policies to address these illegal transactions and enhance financial literacy. This descriptive qualitative study employs an exploratory approach through observation and interviews. After conducting validity tests using audience validation, triangulation, and member checking, the data analysis was performed using NVivo 14. The results indicate that Shopee Pay Later’s accessibility facilitates gestun transactions in Malang City through an easy cash-out mechanism, high cash-out limits, multiple repayment options, simplified transaction processes, and efficient information dissemination. This study also finds that community income influences gestun transactions. Different groups engage in getting funding for various reasons: entrepreneurs use it to obtain business capital, while students and employees use it to cover expenses and fulfill personal desires.